2014
DOI: 10.4314/thrb.v16i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physicochemical characteristics and hygienic practices along the value chain of raw fruit juice vended in Dar es Salaam City, Tanzania

Abstract: Fresh fruit juice is an essential component of human diet and there is considerable evidence of health and nutritional benefits. However, nature of the fruits used in juicing and unhygienic processes in the value chain may cause poor quality of juice. This cross-sectional study was conducted to assess physicochemical characteristics and hygienic practices along the value chain of raw fruit juice vended in Dar es Salaam, Tanzania. A total of 90 juice vendors were interviewed. Ninety juice samples were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Most of the containers (43.3 %) used to store juice were dirty while 20 % of the selling points were also dirty suggesting of contamination. Disregard of sanitary practices during juice preparation, storage in clean containers and vending in clean environment might be the possible cause of high bacterial load in fruit juices sold along roadsides and bus terminals as previously reported by Nonga et al and Simforian et al [ 8 , 11 ]. This was supported by the high bacterial load in fruit juice samples beyond the recommendations.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Most of the containers (43.3 %) used to store juice were dirty while 20 % of the selling points were also dirty suggesting of contamination. Disregard of sanitary practices during juice preparation, storage in clean containers and vending in clean environment might be the possible cause of high bacterial load in fruit juices sold along roadsides and bus terminals as previously reported by Nonga et al and Simforian et al [ 8 , 11 ]. This was supported by the high bacterial load in fruit juice samples beyond the recommendations.…”
Section: Discussionmentioning
confidence: 75%
“…According to FAO, street foods have significant nutritional implications for consumers, particularly from middle and low-income sectors of the population [ 5 ]. Street food vendors in developing countries are often unlicensed, untrained in food hygiene and sanitation, and work under crude unsanitary conditions [ 5 – 8 ]. In Tanzania, urbanization accompanied with low wages offered to employees and labourers has led to proliferation of street food vendors who offer cheap meals that is always contaminated by microbes [ 9 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reddi, Naveen Kumar, Balakrishna, and Sudershan Rao (2015) indicated that 92%, 86%, and 64% of the respondents have the practice of hand washing, utensil washing, and storage of cut fruit, respectively. According to Nonga, Simforian, and Ndabikunze (2014), the majority of premises (78.9%) of fruit preparation in Dares Salaam, Tanzania, were found in unhygienic conditions and likely encouraged contamination of juices.…”
Section: Questionnaire Surveymentioning
confidence: 99%